Inside the outbreaks : the elite medical detectives of the epidemic intelligence service - Pendergrast, Mark. (Boston : Houghton Mifflin Harcourt, 2010)
A history of the elite medical corps at the forefront of the world's most dangerous epidemics cites their victories over such diseases as polio, cholera, and smallpox.
Keywords: Epidemiology -- Popular works; Epidemiologists -- United States; Communicable Disease Control; History, 20th Century -- United States; United States Government Agencies -- United States